(untitled) (Journal of Economic Research & Business Administration, 2015)
This article is written about the importance of ensuring the economic safety of agriculture of Kazakhstan in anticipation of joining to WTO. It has been shown a number of contradictions of Kazakhstan between EU countries, the Customs union, and also import dependence of Kazakhstan by many types of production.For the solution of the above problems the state needs undertake appropriate measures timely, using the state target programs and by that ensure economic safety of the country.